TINJAUAN SOSIOLOGIS TERHADAP NOVEL DETIK TERAKHIR KARYA KARYA ALBERTHIENE ENDAH - ADAMPE, REGINA YOLANDA (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2015)
ABSTRACT The objectives to be achieved in this research are: (1) describe the sociological aspects of literary mimesis in novel Detik Terakhir, in terms of character and characterization, social status, the behavior of the characters, and events that occur in Novel. (2) The extent to which the involvement of the author in the novel Detik Terakhir. This study is a review of sociology of literature using qualitative methods. Research techniques include the stage of data collection, data analysis, data presentation, and conclusion. The data source consists of primary data (novel Detik Terakhir) and a secondary form books of literature and other sources. The results Showed that the sociological aspects of mimesis in the novel Detik Terakhir is a clone of the state of young people today, where many young people are caught in the vortex of drugs as a form of escape from the problems that they face . While the implications of authorship or involvement of the author in the novel Detik Terakhir includes pouring her heart by concern over the unpreparedness of the family and the environment in receiving back a family member who has been rehabilitated drug. Keywords : sociology of literature, mimesis, qualitative, Novel Detik Terakhir